2021
DOI: 10.1093/nar/gkab443
|View full text |Cite
|
Sign up to set email alerts
|

Altering transcription factor binding reveals comprehensive transcriptional kinetics of a basic gene

Abstract: Transcription is a vital process activated by transcription factor (TF) binding. The active gene releases a burst of transcripts before turning inactive again. While the basic course of transcription is well understood, it is unclear how binding of a TF affects the frequency, duration and size of a transcriptional burst. We systematically varied the residence time and concentration of a synthetic TF and characterized the transcription of a synthetic reporter gene by combining single molecule imaging, single mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 117 publications
(234 reference statements)
1
62
0
Order By: Relevance
“…Previously, accumulations of long-bound TF molecules in clusters have been suggested to present transcriptional ‘hot-spots’ with high RNA Polymerase II activity [ 7 , 43 , 44 ]. In order to visualize Halo-SRF accumulations in clusters we performed TALM (tracking and localization microscopy; figure 5 ), which allows for high-resolution localization and diffusion analysis of single proteins in living cells [ 33 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, accumulations of long-bound TF molecules in clusters have been suggested to present transcriptional ‘hot-spots’ with high RNA Polymerase II activity [ 7 , 43 , 44 ]. In order to visualize Halo-SRF accumulations in clusters we performed TALM (tracking and localization microscopy; figure 5 ), which allows for high-resolution localization and diffusion analysis of single proteins in living cells [ 33 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we compared the binding behaviour of RBPJ and RBPJL in the nucleus of live cells using single-molecule tracking ( Figure 4 C and Methods) [ 31 , 33 ]. To visualize single molecules, we created HeLa cell lines stably expressing RBPJ or RBPJL fused to a HaloTag [ 40 ], which we labeled with the organic dye SiR before imaging [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microscope setup: A custom-built fluorescence microscope (as described previously [ 31 ]) was used for single-molecule imaging. It contained a conventional Nikon body (TiE, Nikon) and was equipped with a 638 nm laser (IBEAM-SMART-640-S, 150 mW, Toptica), AOTF (AOTFnC-400.650-TN, AA Optoelectronics) and a high-NA objective (100×, NA 1.45, Nikon).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-particle tracking (SPT) methods have been used to study dynamic TF-DNA interactions and to assess the role of TFs in shaping the chromatin mobility landscape in living eukaryotic cells (19)(20)(21)(22)(23)(24)(25). Most of these studies showed that the residence time of DNA-bound TFs affects the temporal expression patterns of transcription (19,23,24) and the spatial organization of chromatin in live cells (20,22). This shows the importance of residence times as a biophysical characteristic for regulating transcriptional activity and genome organization.…”
Section: Introductionmentioning
confidence: 99%